Health‐related quality of life outcomes for the LEAP study—CALGB 70305 (Alliance): A lymphedema prevention intervention trial for newly diagnosed breast cancer patients. Issue 2 (20th October 2020) - Naughton, Michelle J.; Liu, Heshan; Seisler, Drew K.; Le‐Rademacher, Jennifer; Armer, Jane M.; Oliveri, Jill M.; Sloan, Jeffrey A.; Hock, Karen; Schwartz, Michael; Unzeitig, Gary; Melnik, Marianne; Yee, Lisa D.; et al.
Abstract : Background: Lymphedema is an adverse effect of breast cancer treatment that causes swelling and pain in the arm and hand. We tested 2 lymphedema prevention interventions and their impact on health‐related quality of life (HRQOL) in a group‐randomized trial at 38 cooperative group sites within the United States. Methods: Patients were recruited before breast surgery. Sites were randomly assigned to education‐only (EO) lymphedema prevention or education plus exercise and physical therapy (LEAP). Lymphedema was defined as a ≥10% difference in arm volume at any time from baseline to 18 months postsurgery. HRQOL was assessed using the Functional Assessment of Cancer Therapy–Breast plus 4 lymphedema items (FACT‐B+4). Longitudinal mixed model regression analysis, adjusting for key demographic and clinical variables, examined participants' HRQOL by intervention group and lymphedema status. Results: A total of 547 patients (56% LEAP) were enrolled and completed HRQOL assessments. The results revealed no differences between the interventions in preventing lymphedema ( P = .37) or HRQOL (FACT‐B+4 total score; P = .8777). At 18 months, the presence of lymphedema was associated with HRQOL at borderline significance ( P = .0825). However, African American patients reported greater lymphedema symptoms ( P = .0002) and better emotional functioning ( P = .0335) than patients of other races or ethnicities. Lower HRQOL during the intervention was associated with younger age ( P ≤ .0001), Eastern Cooperative Oncology Group performance status >0 ( P = .0002), ≥1 positive lymph nodes ( P = .0009), having no education beyond high school ( P < .0001), having undergone chemotherapy ( P = .0242), and having had only axillary node dissection or sentinel node biopsy versus both ( P = .0007). Conclusion: The tested interventions did not differ in preventing lymphedema or in HRQOL outcomes. African American women reported greater HRQOL impacts due to lymphedema symptoms than women of other races or ethnicities. Abstract : Two tested lymphedema prevention interventions did not differ in prevention of lymphedema or in quality of life outcomes. African American women, however, reported more lymphedema symptoms than women of other races and ethnicities.